Palliative care communication between patients with intellectual disabilities and hospice staff: a Conversation Analysis pilot study protocol - Irene Tuffrey-Wijne; Andrea Bruun (BMJ Open)
Introduction Communication challenges are among the main barriers for people with intellectual disabilities in accessing palliative care. They include inadequate skills among staff and difficulties with confirming understanding and around the presentation and assessment of symptoms. In-depth analysis of interactions between people with an intellectual disability and staff may shed light on these communicative challenges as well as facilitators. However, no studies have closely analysed the interactions between people with an intellectual disability and professionals within palliative care settings.Methods and analysis This protocol describes a pilot study assessing the feasibility and acceptability of conducting a Conversation Analysis study involving video-recording palliative care conversations between people with intellectual disabilities and professionals.Three conversations between patients with an intellectual disability, their companions and palliative care staff will be video recorded in a UK hospice. Recordings will be transcribed and analysed using Conversation Analysis. Communication phenomena of interest and worth further exploration will be identified in collaboration with key stakeholders.Ethics and dissemination The study received a favourable opinion by a UK research ethics committee in February 2025. All participants must provide informed consent to take part in the study. It will be carefully assessed that potential participants with an intellectual disability have capacity to consent to take part. Accessible study information materials for participants with an intellectual disability are available (ie, easy-read and video).Study findings will be disseminated in academic papers and conference presentations. Progress and findings will also be shared via social media and with relevant groups of people with intellectual disabilities, family carers, service providers and academics.